Nonstationary System Analysis Methods for Underwater Acoustic Communications. (8th February 2011) - Josso, Nicolas F.; Zhang, Jun Jason; Papandreou-Suppappola, Antonia; Ioana, Cornel; Duman, Tolga M.
Abstract : The underwater environment can be considered a system with time-varying impulse response, causing time-dependent spectral changes to a transmitted acoustic signal. This is the result of the interaction of the signal with the water column and ocean boundaries or the presence of fast moving object scatterers in the ocean. In underwater acoustic communications using medium-to-high frequencies (0.3–20 kHz), the nonstationary transformation on the transmitted signals can be modeled as multiple time-delay and Doppler-scaling paths. When estimating the channel, a higher processing performance is thus expected if the techniques used employ a matched channel model compared to those that only compensate for wideband effects. Following a matched linear time-varying wideband system representation, we propose two different methods for estimating the underwater acoustic communication environment. The first method follows a canonical time-scale channel model and is based on estimating the coefficients of the discrete wideband spreading function. The second method follows a ray system model and is based on extracting time-scale features for different ray paths using the matching pursuit decomposition algorithm. Both methods are validated and compared using communication data from actual underwater acoustic communication experiments.